PERAN BUDAYA ORGANISASI DALAM MENINGKATKAN RETENSI KARYAWAN - Shierli Wijaya (STIE Wiyatamandala, 2022)
The study of organizational culture is interesting because it deals with the uniqueness, the characteristics that distinguish one organization from another. Organizational culture is a system of shared meaning held by members that distinguishes an organization from other organizations. This system of shared meaning is a set of key characteristics that organizations uphold. Organizational culture is created by the